Extensive neuritis ossificans of the sciatic nerve: Systematic review and illustrative case. (April 2022) - Yuga, Ann Camille Q.; Pascual, Juan Silvestre G.; Valparaiso, Apple P.; Khu, Kathleen Joy O.
Highlights: Neuritis ossificans is a rare disease with only 17 previously reported cases. There are only 2 prior reports of it occurring in the sciatic nerve. The exact pathophysiology is unknown, but current theories center on trauma, repetitive stretch, and neuroinflammation. The optimal management paradigm has yet to be determined but may consist of conservative medical symptom management or surgical resection. We report the third case of neuritis ossificans in the sciatic nerve, with a good outcome at 13 months after undergoing safe maximal surgical resection. Abstract: Background: Neuritis ossificans is a rare disease described as heterotopic calcification that occurs in neural tissue such as nerves. Method: A systematic review of the literature was done in accordance with PRISMA guidelines. An illustrative case of neuritis ossificans of the sciatic nerve in an 18 year old man was also reported. Results: The review yielded 17 previously reported cases of neuritis ossificans. There was a male predominance and the most common locations were the median and tibial nerves. Only 2 previous cases involved the sciatic nerve. Most were treated with excision with positive outcomes. Our case was treated initially with a biopsy, then partial excision and symptomatic management with NSAIDs and GABA inhibitors. He had a good outcome at 13 months follow-up. Conclusion: Neuritis ossificans is a rare disease with unclear pathophysiology that has been theorized to involve neuroinflammation. Treatment consists of excision, if deemed possible, and symptom control.